SCIENTIFIC-METHODICAL APPROACHES TO ASSESSING THE LEVEL OF FINANCIAL INCLUSION BY REGION (Marketing Journal, 2025)
This article analyzes the scientific and methodological foundations for assessing the level of financial inclusion across regions. The study explores modern methodological approaches to calculating the financial inclusion index, including the construction of a multidimensional index, principal component analysis (PCA), and the integration of digital financial services. The article examines the applicability of methodologies developed by the World Bank, the International Monetary Fund, and other internationa l organizations within regional contexts. The analysis reveals that a comprehensive approach combining access, usage, and quality dimensions provides effective results in evaluating the level of financial inclusion. 646
Keywords: financial inclusion; index methodology; regional analysis; principal component analysis; digital financial services; developing countries